2020
DOI: 10.7150/jca.45494
|View full text |Cite
|
Sign up to set email alerts
|

Inward Tension of Talin and Integrin-related Osmotic Pressure are involved Synergetically in the Invasion and Metastasis of Non-small Cell Lung Cancer

Abstract: The integrin receptor protein talin plays vital roles in intracellular chemical and mechanical activities, and it is implicated in the high invasion and poor prognosis of non-small cell lung cancer (NSCLC). To better understand the mechanism underlying the function of talin in NSCLC invasion and metastasis, a few newly designed tension probe based on Förster resonance energy transfer was used for real-time observation of tension changes in A549 cells. High NSCLC cell aggressiveness was found to be accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Investigation of the contribution of talin to cancer progression is timely. During this study ~ 670 more cancer-associated talin-1 point mutations have been added to the COSMIC database ( Supplementary Fig.S1) and there are recent studies discussing the connection between talin and cancer 23,[55][56][57][58] . The work we present here demonstrates an efficient and fast pipeline approach using bioinformatics tools to characterise future talin mutations identified in cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the contribution of talin to cancer progression is timely. During this study ~ 670 more cancer-associated talin-1 point mutations have been added to the COSMIC database ( Supplementary Fig.S1) and there are recent studies discussing the connection between talin and cancer 23,[55][56][57][58] . The work we present here demonstrates an efficient and fast pipeline approach using bioinformatics tools to characterise future talin mutations identified in cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of techniques have been employed to study oncotic and hydrostatic pressures in cancer. Different cancer studies have included adenocarcinoma [ 66 ], breast [ 67 ], colorectal [ 68 ], esophageal [ 69 ], head and neck [ 70 ], lung [ 71 ], melanoma [ 68 ], ovarian [ 72 ], prostate [ 73 ], and skin [ 74 ]. The variations in hyper- and hypo-osmotic states contributing to the tumorgenicity of the different cancers demonstrates the importance of regulating homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytic pyroptosis displays membrane blebbing, cell swelling, and further promotes pore formation on the astrocyte membrane, which exacerbates membrane permeabilization (5)(6)(7). Alterations of cell shape depend on cytoskeleton remodeling, which provides the cytoskeletal tractive forces against the outward osmotic pressure (OP) across the membrane (8)(9)(10). Our previous study suggested that the production of protein nanoparticles (PNs) in astrocytes upregulates cell osmolarity significantly by adsorbing cations and driving the influx of ions and water, thereby promoting cell swelling (8).…”
Section: Introductionmentioning
confidence: 99%